A Novel Method for Placing the Sensors for Noncircular Sources in DOA Estimation to Reduce the Mutual Coupling - Patra, Rajen Kumar; Dhar, Anindya Sundar (2023 3rd International Conference on Range Technology (ICORT), 2023)
In this paper, we present a novel method of placing the sensors of a sparse array for non-circular sources in direction-of-arrival (DOA) estimation. We know that for non-circular sources, the elliptic covariance is not equal to zero and we can we can exploit the sum and the difference coarray (SDCA) of the sparse array by implementing the spatial smoothing MUltiple Signal Classification (MUSIC) algorithm. The resulting sparse structure can significantly mitigate the mutual coupling effect of the original configuration without reducing the degrees of freedom (DOF) it achieves. As the mutual coupling of the generated configuration reduces, its DOA estimation performance also improves than the original configuration. All the required simulations are carried out to evaluate the superiority of the proposed method.